International taxation of trust income - Brabazon, Mark (UK Cambridge University Press, 2019)
"This book presents the principles and design of international taxation of trust income and distributions as a coherent subject of international tax law. It begins with the trust tax rules and international settings of four countries -- Australia, New Zealand, the United Kingdom and the United States -- focusing on the attribution of trust income to the grantor/settlor, the beneficiary or the trust entity, trust residence, and the taxation of trust distributions. Having identified the international taxing principles that those countries apply to trusts, it infers a range of principles and settings that may be applied by countries generally and examines how the interaction of those settings may lead to double- or non-taxation overall. Consideration is given to conflicts of attribution, hybridity and fiscally homeless trusts. The book examines the interaction of tax laws in non-treaty and treaty situations and puts these interactions in context as part of the broader international tax order and recommendations of the OECD/G20 BEPS project. It proposes an approach to tax design based on an ordered overview of different taxing claims and the interests which they represent, respect for the fiscal sovereignty of countries concerned, and recognition of the differing roles of national laws and tax treaties"--
Introduction -- The grantor -- The beneficiary -- The trust -- Distributions -- International taxation -- The international tax order and the interaction of tax laws -- Treaties -- Conclusions and proposals : taxing the shadow.
Includes bibliographical references (pages 346-356) and index.
Keywords: Trusts and trustees -- Taxation -- Law and legislation; Income tax -- Law and legislation; LAW / Taxation